The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/clc.23538
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand syndrome and factor VIII in patients with moderate to severe mitral regurgitation undergoing transcatheter mitral valve repair

Abstract: Background and Hypothesis The acquired von Willebrand syndrome (AvWS), which predisposes to bleeding events, is often related to valvular heart diseases. We investigated possible implications of AvWS and factor VIII levels in patients with moderate to severe mitral regurgitation (MR) undergoing transcatheter mitral valve repair (TMVR). Methods and Results 123 patients with moderate to severe MR were prospectively enrolled. Complete measurements of von Willebrand Factor activity (vWFAct), von Willebrand Factor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(37 reference statements)
0
6
1
Order By: Relevance
“…There are reports of moderate or severe native mitral regurgitation to be associated with abnormal VWF multimers and clinically significant GI bleeding, which reversed after mitral valve surgery [ 15 ]. In 123 patients with moderate or severe native mitral regurgitation undergoing transcatheter mitral valve repair, Meindl et al reported that an elevated mean mitral valve gradient following transcatheter mitral valve repair was associated with a low post-procedure VWF activity [ 16 ]. However, this alteration did not translate into a higher incidence of bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of moderate or severe native mitral regurgitation to be associated with abnormal VWF multimers and clinically significant GI bleeding, which reversed after mitral valve surgery [ 15 ]. In 123 patients with moderate or severe native mitral regurgitation undergoing transcatheter mitral valve repair, Meindl et al reported that an elevated mean mitral valve gradient following transcatheter mitral valve repair was associated with a low post-procedure VWF activity [ 16 ]. However, this alteration did not translate into a higher incidence of bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of moderate or severe native mitral regurgitation to be associated with abnormal VWF multimers and clinically signi cant GI bleeding, which reversed after mitral valve surgery (12). In 123 patients with moderate or severe native mitral regurgitation undergoing transcatheter mitral valve repair, Meindl et al reported that an elevated mean mitral valve gradient following transcatheter mitral valve repair was associated with a low post-procedure VWF activity (13). However, this alteration did not translate into a higher incidence of bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…The bleeding is typically attributed to gastrointestinal angiodysplasia, fragile and abnormal vessels immediately beneath the mucosa [ 8 ]. In addition to , hypertrophic obstructive cardiomyopathy [ 9 ], pulmonary hypertension [ 10 ], congenital structural heart diseases [ 11 ], mitral regurgitation (MR) [ [12] , [13] , [14] , [15] , [16] ], and mechanical circulatory support [ 17 , 18 ] have also been previously reported to cause AVWS.…”
Section: Introductionmentioning
confidence: 99%
“…MR has been reported as a cause of AVWS in several studies [ [12] , [13] , [14] , [15] , [16] ]. Blackshear et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation